P065 Conservation of breast milk cytokine profiles in consecutive pregnancies of women with inflammatory bowel disease. (27th May 2021) - Agrawal, M; Tarassishin, L; Rendon, A; Debebe, A; Hillenbrand, C; White, S; Eisele, C; Hawkins, K; Chen, C L; Kornbluth, A; George, J; Legnani, P; et al.
Abstract: Background: Preliminary evidence suggests changes in breast milk cytokines in women with inflammatory bowel disease (IBD) compared to healthy controls, with potential implications toward offspring immunological development. However, changes in breast milk cytokine profiles in consecutive pregnancies are not known. Methods: In this pilot study, we prospectively enrolled 11 pregnant women with, and 10 without IBD during two consecutive pregnancies and collected clinical data during each pregnancy and post birth. We collected breast milk samples at two weeks post birth and obtained the expression levels of 92 cytokines using the Olink proteomic platform. We further analyzed the correlation of cytokine profiles within each sample, in paired breast milk samples from consecutive pregnancies, and in random two unpaired breast milk samples, of women with and without IBD. Results: The baseline characteristics of women with and without IBD were comparable (Table). The cytokine profiles were significantly correlated between paired breast milk samples from consecutive pregnancies compared to unpaired breast milk samples from women with or without IBD. The overall correlations of cytokine profiles in paired IBD pregnancies were significantly higher than the controls (Figure). Conclusion: Our pilot study results suggest that the breast milk cytokine signatures are more conserved in consecutive pregnancies of women with IBD compared to those without IBD. Future analysis will test if our findings have implications toward familial clustering of immune functions in offspring.